Financial regulation and risk management: addressing risk challenges in a changing financial environment - Ojo, Marianne (Munich Personal RePEc Archive, 2025)
Will the April 2nd Announcement generate its intended objectives? It’s still early days – however, it appears increasingly likely that negotiation outcomes – particularly between those significantly impacted by the Announcement, will be a major determinant in deciding whether the tariff hikes resulting from the April 2nd Announcement, will be short or long term. As of the 11th April, 2025, President Trump’s universal tariffs on China had amounted to 145% whilst China announced tariffs of 125% on U.S imports. Amongst other things, this paper aims to address complexities and challenges faced by regulators in identifying and assessing risk, problems arising from different perceptions of risk, and solutions aimed at countering problems of risk regulation. It will approach these issues through an assessment of explanations put forward to justify the growing importance of risks, well known risk theories such as cultural theory, risk society theory and governmentality theory. In addressing the problems posed as a result of the difficulty in quantifying risks, it will consider a means whereby risks can be quantified reasonably without the consequential effects which result from the dual nature of risk that is, risks emanating from the management of institutional risks.
Keywords: Financial Forecasting and Simulation; General Financial Markets; International Financial Markets; Regulation and Business Law

The effects of Basel III on the intermediation and market activities of WAEMU banks - Kouakou, Thiédjé Gaudens-Omer (University Library of Munich, Germany, 2025)
This paper analyzes the effect of Basel III adapted to WAEMU on the behavior of banks in the zone (intermediation and market activities). After having developed a model for optimizing the return on bank equity, under various constraints (balance sheet constraints, Basel III regulatory constraints), we resort to linear programming via the Danzig simplex algorithm and to a structure of reasonable rates to obtain the optimal values of the various bank balance sheet items. The results, obtained by comparing these theoretical values with the values observed before Basel III (before January 1, 2018), show an increase in the supply of loans, obtained not only from deposits and bank refinancing but also via resources from the financial markets. We can also observe the intuitive result of an increase of bank reserves in line with the constraint that Basel III imposes on banks to increase their liquidity. In short, Basel III tends to strengthen bank financing in the zone, while improving the soundness of banks through the constitution of larger reserves.
Keywords: Calibration; Credit supply; Linear programming; Prudential regulation

Arbitration as a Legal Mechanism in the Settlement of Disputes under Cameroonian Law - Tambe, Hans; Forbi, Nduah Esther; Epie, Mousinga Adele (Social Science Research Network, 2021)
Recently, commercial activities in the state of Cameroon are evolving and there is an inflow of investors from within the OHADA Zone and other regions of the world to Cameroon. This has led to the proliferation of commercial contracts such as concession contracts, production sharing agreements, risk contracts between the Republic of Cameroon and foreign investors, or contracts between individuals of foreign countries as well as with Cameroonian nationals. Commonly, contracts may be breached and disagreements surface among the contracting parties. The difficulties pose is in the manner to settle such disagreements in a friendly manner to maintain the relationship between the parties and to enables the contracting parties to resolve the disputes more cost-effectively and increase business efficiency in Cameroon. However, the state of Cameroon has a favorable attitude towards bilateral and multilateral investment treaties to guarantee protection to investors in the territory. This elucidates the reason why the government of Cameroon has enacted laws and ratified regional and international treaties, aimed at safeguarding a smooth atmosphere for investors and other commercial traders particularly in the domain of arbitration to help in resolving disputes in case of any disagreement among contracting parties. This article will present the authorities involved in arbitration with the experience regarding the application of the various law and institutions concerned with the arbitration. This will also help contracting parties or investors to understand the legal mechanisms in the settlement of disputes through arbitration in Cameroon.
Keywords: Arbitrage; Arbitragem; Arbitration; dispute; legal; mechanism; settlement

Legal Protection of Foreign Direct Investment in the OHADA Area - Ngoya, Dominique (Social Science Research Network, 2021)
This paper analyzes the protection of Foreign Direct Investments in the OHADA area, specifically, its regulation by the Treaty of Organization and Harmonization in Africa of Business Law (OHADA Treaty). It is to restore legal and judicial security within their scope that OHADA member countries have undertaken to harmonize and unify their economic sector legislation to attract foreign investment as a factor in economic development. Several national and international legal instruments are responsible for the protection of foreign direct investment in OHADA countries. Indeed, the volume of foreign direct investment (FDI) to developing countries increased considerably during the 1990s; As Africa is now one of the favorite destinations for Western and even African investors, it is becoming a very profitable continent for investors. However, the issue of regulating or securing foreign investment in African countries is still flawed. The establishment of OHADA, in a way, is in the same direction; if we stick to the purpose of the organization prescribed in paragraph 5 of the preamble to the OHADA Treaty, which states that the purpose of the OHADA law is to "promote the growth of economic activity and encourage investment." Unfortunately, this objective remains only an announcement of the preamble to the Treaty, because of the definition of business law given by Article 2 of that treaty. However, the list of subjects is not exhaustive, investment remains absent. Thus, foreign investment is not regulated by the OHADA Treaty, so even investment-related activities are held by other subjects (corporate law, commercial law, and security law). The omission of FDI in the scope of the OHADA Treaty leads us to raise the question of its regulation.This work proposes a reflection that the OHADA Treaty should be modernized through reform including investment and many other issues to deal effectively with the issue of foreign investment given the ineffectiveness of national and sub-regional instruments in this area.
Keywords: Foreign direct investment; Investment Law; Investment Protection; OHADA

The Effectiveness of the Harmonization Tool Adopted Under the Ohada Regime - Ceesay, Buba (Social Science Research Network, 2020)
The Organization for the Harmonization of Business Law in Africa, OHADA, is a regional entity whose primary objective is to harmonize the Business Law of its members. It has adopted legislative measures and institutional setups to ensure the realization of this object. This paper critically examined the effectiveness of the harmonization tool adopted under OHADA. The paper first gives a brief overview of OHADA setups, then the advantages and shortcomings of the harmonization tool adopted under the OHADA regime and finally concluded that though OHADA is a major step towards the attainment of harmonization of business law and Integration with the view of fostering development and business activities, its harmonization tool is lacking full efficacy towards the attainment of the objectives of the organization due to prevailing limitations and challenges.
Keywords: SSRN

60 Years of the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards 1958: Are We There Yet in Sub-Saharan Africa? - Okubote, Abayomi (Social Science Research Network, 2018)
Sub-Saharan Africa has, in recent years, been classified as a natural-resource play for foreign investors. These investment potentials have made the region one of the most attractive investment destinations in the world. The region is also diverse, with a mix of different legal systems and legal traditions. While investors are constantly seeking to understand the different legal regimes, international arbitration offers comfort by providing a framework for the enforcement of rights in a neutral forum and on a different platform. According to the World Bank, the ability to enforce an arbitral award is an important factor for investors considering potential markets in which to invest.Given the sixtieth anniversary celebration of the New York Convention (NY Convention), this article examines the enforcement regimes for arbitral awards in sub-Saharan Africa. It considers the momentous developments in the enforcement regimes in the region, due to the implementation of the NY Convention. It examines the proposed amendments to the enforcement provisions in the Nigerian Arbitration Act (Repeal and Re-enactment) Bill 2017, recently passed by the Nigerian Senate. It also examines the important provisions in the revised Uniform Act on the Law of Arbitration and the revised Rules of Arbitration of the Common Court of Justice and Arbitration – both recently adopted by the OHADA Council of Ministers. It attempts a comparison between the enforcement regimes in the OHADA Member States, the NY Convention Member States, and in countries that do not belong to any of the two regimes.A chart of the legal regimes on enforcement of foreign arbitral awards in sub-Saharan Africa is attached as appendix.
Keywords: ACA; Annulment; Arbitral Awards; CCJA; Commercial Arbitration; Convention; Enforcement; Enforcement of Arbitral Awards; Foreign Awards; ICSID Convention; Judiciary; New York Convention; OHADA; Reciprocity; Reservations; Sub-Saharan Africa; Treaty; UAA; UNICTRAL Model law

The Enforcement of Arbitral Awards in Cameroon - Tumnde, Taylor (Social Science Research Network, 2013)
The increase in international trade creates a growing number of disputes between parties from different countries. Arbitration has become the most preferred mechanism to solve disputes in international trade. If a party does not voluntarily comply with an award, the successful party must apply for recognition and enforcement of the award in order to obtain the remedies. Cameroon is one of the major business markets in West and Central Africa, several companies committed to arbitral procedures are likely to have assets in Cameroon. This means that if a party fails to honour an award, an enforcement procedure may begin within a Cameroonian court. The enforcement procedures in Cameroon are sufficient and do comply with international standards. The most used and important instruments for recognition and enforcement are the United Nations Convention on the Recognition and Enforcement of Foreign Arbitral Awards of 1958 and the Uniform Act on Arbitration 1999 in the OHADA territory, to which Cameroon is a signatory State. According to this Convention and the Uniform Act, an arbitral award may be refused enforcement under certain grounds laid down in them. There are various types of arbitral awards contemplated by the Cameroonoan legislature and will be herein examined to see how they can be enforced in Cameroon. An analysis of the legal situation in Cameroon confirms that there are problems associated with the enforcement of arbitral awards. These problems are not, however, connected with the concept of arbitral awards, but rather with the entire judicial system in Cameroon. Even though an enforcing party can do little to overcome these problems, certain measures can be taken in order to ease the enforcement procedure
Keywords: Arbitrage; Arbitragem; Arbitral Awards; Arbitration; Cameroon; Enforcement; OHADA

Demand Guarantees Under the OHADA Uniform Act on Securities - Enonchong, Nelson (Social Science Research Network, 2008)
This paper seeks to assess the extent to which the provisions of the Uniform Act dealing with demand guarantees meet the OHADA objective of modernisation to facilitate commercial activity. It notes that in general those provisions are to be welcomed as a helpful contribution towards the aforementioned OHADA objectives. However, it argues that there is scope for some improvement and that a revision of the provisions is desirable, primarily to give the parties greater commercial flexibility by allowing them more freedom of contract and to reduce the areas of uncertainty and confusion. It is proposed to consider the key benefits brought about by the Uniform Act before identifying and explaining the main areas of concern.
Keywords: Demand guarantees; OHADA Uniform Act on Securities